ANALISIS PENGGUNAAN METODE MENGAJAR GURU MATA PELAJARAN SOSIOLOGI KELAS X IPS A SMANSA NGABANG - Yohanes Iwanto; Sulistyarini Sulistyarini; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aims to determine the use of teacher teaching methods on sociology subjects in class X IPS A Ngabang 1 Public High School. The research method used is descriptive. Data collection techniques in this study were observation, interviews and documentation studies. In this research, the data source was sociology teacher in class X IPS A Ngabang 1 Public High School. The results show that the use of the lecture method by the teacher has been used each time teaching in class X IPS A. In presenting the subject matter to students using the lecture method, the teaching facilities used by the teacher are LKS and the selection of the use of lecture methods is based on student factors, subject matter and teaching facilities. The use of the question and answer method by the teacher has been used each time carrying out learning in class X IPS A. As long as the learning activities take place using the question and answer method, only a few students actively ask and answer their questions. In addition, the selection of the question and answer method is based on the characteristics of the learning material. The teaching facilities used by the teacher are LKS. Keywords: Teaching Method, Lectures, Question and Answer